Forensic analysis and sequence variation of 133 STRs in the Hakka population - Feng, Yuhang; Zhao, Yutao; Lu, Xiaoyu; Li, Haiyan; Zhao, Kai; Shi, Meisen; Wen, Shaoqing (Frontiers in Genetics, 2024)
Short Tandem Repeats (STRs) are highly valuable genetic markers in forensic science. However, the conventional PCR-CE technique has limitations, and the emergence of massively parallel sequencing (MPS) technology presents new opportunities for STR analysis. Yet, there is limited research on Chinese population diversity using MPS. In this study, we obtained genotype data for 52 A-STRs and 81 Y-STRs from the Hakka population in Meizhou, Guangdong, China, using the Forensic Analysis 2 System Multiplecues SetB Kit on the MGISEQ-2000 platform. Our findings demonstrate that these 133 STRs are highly efficient for forensic applications within the Meizhou Hakka population. Statistical analysis revealed Hobs values ranging from 0.61306 to 0.91083 and Hexp values ranging from 0.59156 to 0.91497 for A-STRs based on length polymorphism. For sequence polymorphism, Hobs values ranged from 0.61306 to 0.94586, and Hexp values fluctuated between 0.59156 and 0.94487. The CPE values were 1-5.0779620E-21 and 1-3.257436E-24 for length and sequence polymorphism, respectively, while the CPD values were 1-1.727007E-59 and 1-5.517015E-66, respectively. Among the 80 Y-STR loci, the HD values for length and sequence polymorphism were 0.99764282 and 0.99894195, respectively. The HMP values stood at 0.00418102 and 0.00288427, respectively, and the DC values were 0.75502742 and 0.83363803, respectively. For the 52 A-STR loci, we identified 554 and 989 distinct alleles based on length and sequence polymorphisms, respectively. For the 81 Y-STR loci, 464 and 652 unique alleles were detected at the length and sequence level, respectively. Population genetic analysis revealed that the Meizhou Hakka population has a close kinship relationship with the Asian populations THI and KOR based on length polymorphism data of A-STRs. Conversely, based on length polymorphism data of Y-STRs, the Meizhou Hakka population has the closest kinship relationship with the Henan Han population.Overall, the variation information of repeat region sequences significantly enhances the forensic identification efficacy of STR genetic markers, providing an essential database for forensic individual and paternity testing in this region. Additionally, the data generated by our study will serve as a vital resource for research into the genetic structure and historical origins of the Meizhou Hakka population.